ANTIFUNGAL ACTIVITY OF A SECONDARY METABOLITE OF AZADIRACHTA INDICA AND ITS DERIVATIVES â€“ AN IN SILICO STUDY - Nagesh, Simhadri Vsdna; M, Muniappan; I, Kannan; S, Viswanathan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: This study was aimed to inhibit the 1, 3 Î²-glucan synthase with azadirachtin or with the derivatives by docking method. Methods: The homology model of the protein 1, 3 Î² glucan synthase was prepared with easy modellarâ€ using query sequence and template and it was validated with procheck of Ramachandran plot. The ligand was selected from the PubChem database, and the .sdf file was downloaded which was converted to another file format with open babel. The .pdb files of protein and ligand were uploaded for rough docking with iGEMDOCK, and finally, the accurate docking was made with autodock vina. The docked poses were visualized with PYMOL then saved. The derivatives of the ligand were generated with SWISS ADME, free online software, and selected the derivative for docking. Results: The results obtained from iGEMDOCK and Autodock Vina were tabulated. It was found out that the Azadirachtin and the derivatives are effective in binding 1, 3 Î² Glucan synthase and thereby inhibiting the formation and integrity of fungal cell wall. Conclusion: In this study, the secondary metabolite Azadirachtin and the derivatives are showing inhibitory action against the model protein 1, 3 Î² glucan synthase and it was suggested that the external application of the ligand and its derivatives can be used because of their poor oral bioavailability.